PELAKSANAAN TERA ULANG SEBAGAI UPAYA PERLINDUNGAN KONSUMEN DALAM MENEKANKAN KECURANGAN SPBU “PASTI PAS!” DI PROVINSI BALI - Pradita Hananta, Didit; Supasti Darmawan, Ni Ketut; -, Marwanto (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
The presence of the General Fuel Filling Station, also called SPBU is closely related to people in their daily lives. SPBU (the term for gas station in Indonesia) is actually an extension of the Pertamina Company which now focuses things on transforming in all areas, which provide the best services with the term they use is ”Pertamina Way". Gas stations that have successfully implementing the Pertamina Way is eligible for certification "Pasti Pas!". However, many announcement from mass media that says some kind of fraud is committed by some gas station nowdays. Altough, the protection of consumers from fraudulent that commited by gas station has actually been done by carrying out the “Tera Ulang” system. The purpose of this study is to2determine how the implementation of the “Tera Ulang” system as an effort to the consumer protection and an efforts that done by the consumer in case of fraudulent and penalties given to that gas station. This type of study using an approach that is based on empirical laws.The data which obtained from research in the field shows that despite of “Tera Ulang” has been done but still there are some gas stations that commit fraud. Consumers choose to remain silent and not to make any effort against the gas station that doing fraud. Law punishment for "Pasti Pas!" certificated gas station if found guilty by cheating will be penalized in accordance of applicable law and the reduction or withdrawal of the predicate "Pasti Pas!”.
Keywords: Tera Ulang (Remeasure), Consumer Protection, Sanctions, Fraud Of SPBU